2020
DOI: 10.3390/molecules25143278
|View full text |Cite
|
Sign up to set email alerts
|

Novel Insights into Mercury Effects on Hemoglobin and Membrane Proteins in Human Erythrocytes

Abstract: Mercury (Hg) is a global environmental pollutant that affects human and ecosystem health. With the aim of exploring the Hg-induced protein modifications, intact human erythrocytes were exposed to HgCl2 (1–60 µM) and cytosolic and membrane proteins were analyzed by SDS-PAGE and AU-PAGE. A spectrofluorimetric assay for quantification of Reactive Oxygen Species (ROS) generation was also performed. Hg2+ exposure induces alterations in the electrophoretic profile of cytosolic proteins with a significant decrease in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 65 publications
1
22
0
1
Order By: Relevance
“…That HgCl 2 induces protein aggregation has already been reported for other proteins. For example, Arnhold et al 2015 [ 34 ] identified amyloid protein aggregation in the cell nucleus as a novel Hg–bio-interaction pathway [ 34 ], and we, in our previous studies, showed the formation of a mercerized tetrameric Hb as a result of treating human erythrocytes with increasing concentrations of HgCl 2 [ 5 ]. We also investigated the possibility of mercury-induced conformational changes in PL proteins using fluorescence spectroscopy.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…That HgCl 2 induces protein aggregation has already been reported for other proteins. For example, Arnhold et al 2015 [ 34 ] identified amyloid protein aggregation in the cell nucleus as a novel Hg–bio-interaction pathway [ 34 ], and we, in our previous studies, showed the formation of a mercerized tetrameric Hb as a result of treating human erythrocytes with increasing concentrations of HgCl 2 [ 5 ]. We also investigated the possibility of mercury-induced conformational changes in PL proteins using fluorescence spectroscopy.…”
Section: Discussionmentioning
confidence: 89%
“…Although heavy metals are generally present in trace amounts in natural waters, a large number of them are toxic even at very low concentrations [ 1 ], posing a serious danger to marine organisms [ 2 , 3 , 4 ]. Among the various heavy metals, mercury (Hg) has drawn a lot of attention, as it is the most toxic nonessential metal [ 5 ]. Mercury has captured the attention of the scientific community since the 1950s, when the first evidence of hazardous environmental impacts were reported [ 6 ], which led to policies and regulations to limit Hg emissions.…”
Section: Introductionmentioning
confidence: 99%
“…In the life cycle of bivalves, the early developmental stages result in being most susceptible to various pollutants, such as toxic metals [ 8 ], pesticides [ 9 ], and antifouling paints [ 10 ], and it has been demonstrated that the concentrations of toxic metals able to cause lethal toxicity in embryos and larvae are much lower than those that are lethal to adults [ 11 , 12 ]. Among toxic metals, mercury (Hg) is one of the most toxic nonessential metals [ 13 ]. Mercury contamination in seawater is an issue to the environment and human health.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Hg inhibitory activity on the glycolytic enzymes hexokinase and phosphofructokinase has been reported [ 53 ]. Also, membrane proteins are modified by Hg, including tubulin [ 54 ] and erythrocyte (RBC) band 3 and 4.1 and 4.2 proteins [ 55 ].…”
Section: Mercury Exposure and Toxicitymentioning
confidence: 99%
“…It is important to emphasise that the reported Hg-induced damage to hemoglobin (Hb) may also contribute to the decreased bioavailability of this key vasorelaxant molecule [ 130 , 131 ]. A tetrameric mercurized form of Hb, supposed to be dysfunctional in physiological conformational changes crucial for the oxygenation/deoxygenation process, can be observed after RBC exposure to Hg 2+ [ 55 ]. As discussed in the introduction, accessible Cys residues represent the preferential site of Hg–protein interaction.…”
Section: The Role Of Erythrocytes In Hg-induced Endothelium Dysfunctionmentioning
confidence: 99%